PROBLEMS ARISING IN THE COLLECTION OF STATE DUTIES BY CIVIL COURTS - Sulaymonova Nargiza Muxiddinovna (European Science Publishing, 2024)
In connection with the increase in citizens' appeals to the courts in the context of the judicial reform being implemented in our country, some problems began to arise in regulating issues related to legal costs. In particular, there are problems associated with the collection of state duties, starting with going to court and making decisions based on the results of consideration of cases. This article discusses the problems associated with paying state fees when applying to civil courts, and suggests ways to eliminate such problems.
Keywords: legal costs, state duty, collection, material damage, property disputes, moral damage.